Substrate Selectivity and a Novel Role in Inhibitor Discrimination by Residue 237 in the KPC-2 β-Lactamase - Papp-Wallace, Krisztina M. (American Society for Microbiology (ASM), 2010)
β-Lactamase-mediated antibiotic resistance continues to challenge the contemporary treatment of serious bacterial infections. The KPC-2 β-lactamase, a rapidly emerging Gram-negative resistance determinant, hydrolyzes all commercially available β-lactams, including carbapenems and β-lactamase inhibitors; the amino acid sequence requirements responsible for this versatility are not yet known. To explore the bases of β-lactamase activity, we conducted site saturation mutagenesis at Ambler position 237. Only the T237S variant of the KPC-2 β-lactamase expressed in Escherichia coli DH10B maintained MICs equivalent to those of the wild type (WT) against all of the β-lactams tested, including carbapenems. In contrast, the T237A variant produced in E. coli DH10B exhibited elevated MICs for only ampicillin, piperacillin, and the β-lactam-β-lactamase inhibitor combinations. Residue 237 also plays a novel role in inhibitor discrimination, as 11 of 19 variants exhibit a clavulanate-resistant, sulfone-susceptible phenotype. We further showed that the T237S variant displayed substrate kinetics similar to those of the WT KPC-2 enzyme. Consistent with susceptibility testing, the T237A variant demonstrated a lower k(cat)/K(m) for imipenem, cephalothin, and cefotaxime; interestingly, the most dramatic reduction was with cefotaxime. The decreases in catalytic efficiency were driven by both elevated K(m) values and decreased k(cat) values compared to those of the WT enzyme. Moreover, the T237A variant manifested increased K(i)s for clavulanic acid, sulbactam, and tazobactam, while the T237S variant displayed K(i)s similar to those of the WT. To explain these findings, a molecular model of T237A was constructed and this model suggested that (i) the hydroxyl side chain of T237 plays an important role in defining the substrate profile of the KPC-2 β-lactamase and (ii) hydrogen bonding between the hydroxyl side chain of T237 and the sp(2)-hybridized carboxylate of imipenem may not readily occur in the T237A variant. This stringent requirement for selected cephalosporinase and carbapenemase activity and the important role of T237 in inhibitor discrimination in KPC-2 are central considerations in the future design of β-lactam antibiotics and inhibitors.